A gender-responsive treatment facility in correctional services: the development of psychological gymnasium for women offenders - Mak, Vivian W.M. (International journal of offender therapy and comparative criminology, 2018)
With increasing evidence suggesting a disparity in female and male offenders in terms of rehabilitative needs, growing concern has been placed on the development of gender-specific services for female offenders. As such, a prison-based psychological gymnasium (PSY GYM), with distinctive features in integrating cognitive-behavioral and positive-psychology concepts to address female offenders’ needs, was set up in 2011. The present study aims to introduce the concept as well as present findings to evaluate the overall effectiveness of PSY GYM. Nineteen Chinese female offenders participated in a 6- to 8-month intensive training program at the Lo Wu Correctional Institution (LWCI) of the Hong Kong Correctional Services Department in Hong Kong. Psychometric inventories were used to assess their psychological distress and positive growth following the program. Participants showed significant reduction in their depression, anxiety, and stress symptoms, and in their tendency to pay attention to negative information. Furthermore, their sense of hope, gratitude, and tendency to pay attention to positive information had remarkably increased. This indicated the effectiveness of PSY GYM in facilitating successful rehabilitation for female offenders.